MOSQUE-BASED COMMUNITY EMPOWERMENT - Muhammad Jawahir; Badrah Uyuni (Spektra: Jurnal Ilmu-ilmu Sosial, 2019)
This article discusses mosque-based community empowerment carried out by the Al Mahdy Grand Mosque, Jatiranggon Village, Kec. Jatisampurna, Bekasi, by conducting survey and interview methods. The results of this study concluded that the Community Empowerment carried out by the Al-Mahdy Grand Mosque can be felt by the surrounding community through social-based programs and Majelis Taklim with mosque management carried out by DKM or mosque administrators. The ground floor of the mosque is usually used for recitation places, weddings, and other social activities, where these activities, especially weddings, have opened business opportunities for the community around the mosque to improve their economy, either with chattering services, parking services, MC, etc.